2012
DOI: 10.1101/gad.200329.112
|View full text |Cite
|
Sign up to set email alerts
|

G9a/GLP-dependent histone H3K9me2 patterning during human hematopoietic stem cell lineage commitment

Abstract: G9a and GLP are conserved protein methyltransferases that play key roles during mammalian development through mono-and dimethylation of histone H3 Lys 9 (H3K9me1/2), modifications associated with transcriptional repression. During embryogenesis, large H3K9me2 chromatin territories arise that have been proposed to reinforce lineage choice by affecting high-order chromatin structure. Here we report that in adult human hematopoietic stem and progenitor cells (HSPCs), H3K9me2 chromatin territories are absent in pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
136
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(149 citation statements)
references
References 55 publications
12
136
1
Order By: Relevance
“…However, we observed that PRMT7 was not required for immature and mature B cell differentiation in mice with the B cell-specific PRMT7 deletion. A similar case was reported in mice deficient for the lysine methyltransferase G9a, which showed delayed hematopoietic progenitor cell lineage commitment without apparent defects in early lymphocyte development (43,44).…”
Section: Discussionmentioning
confidence: 77%
“…However, we observed that PRMT7 was not required for immature and mature B cell differentiation in mice with the B cell-specific PRMT7 deletion. A similar case was reported in mice deficient for the lysine methyltransferase G9a, which showed delayed hematopoietic progenitor cell lineage commitment without apparent defects in early lymphocyte development (43,44).…”
Section: Discussionmentioning
confidence: 77%
“…29 However, H3K9me2 has been implicated in the terminal commitment of blood, cardiac, retinal, neural, muscle and germline lineages. 23,25,29,[40][41][42][43] For example, H3K9me2 plays a dynamic role in retinal progenitor cells 44 and loss of Ehmt2 mediated epigenetic repression leads to profound defects in the early retina. Zebrafish ehmt2 morphants show severe decreases in crx, neuroD and irbp gene expression; markers of retinal cell differentiation.…”
Section: Canonical Roles Of Ehmt1/2 Complexmentioning
confidence: 99%
“…Recent evidence indicates that the H3K9me2 domains are highly dynamic and important for differentiation and maintaining cell identity (8)(9)(10). Although H3K9me2 marks large domains of mostly transcriptionally silent regions of the genome, small windows of active chromatin have been characterized within the large heterochromatin domains, termed euchromatin islands (EIs) (9,11).…”
mentioning
confidence: 99%